Effects of the Bologna Reform on Educational Outcomes: Micro Evidence from Germany - Sabrina Hahm; Jochen Kluve (Institute for the Study of Labor (IZA), 2016)
The Bologna Process aimed at harmonizing European higher education systems and at increasing their efficiency. This paper analyzes impacts of the Bologna Reform for Germany by using unique micro data from Humboldt-Universität zu Berlin (HU). We estimate treatment effects on the probability to graduate within instructional time, on standardized study duration, and on final overall grades. Variation in treatment introduction over time and across departments generates exogenous assignment of students into a treatment (Bachelor) and control group (Diploma). We account for potentially remaining selection bias by estimating a 2SLS model using the share of first-year Bachelor students among all students as an instrument. Our empirical results are robust across specifications and sample stratifications and indicate the following: the Bologna reform led to a significant and sizeable increase in the probability of graduating within planned instructional time; it also significantly decreased standardized study duration. At the same time, overall final grades are significantly worse in the treatment group.
Keywords: I21; I28; J24; 330; Bologna process; education policy; university reform; impact analysis; instrumental variables